2013
DOI: 10.1021/jm400915j
|View full text |Cite
|
Sign up to set email alerts
|

1-Substituted (Dibenzo[b,d]thiophen-4-yl)-2-morpholino-4H-chromen-4-ones Endowed with Dual DNA-PK/PI3-K Inhibitory Activity

Abstract: Analogues of (dibenzo[b,d]thiophen-4-yl)-2-morpholino-4H-chromen-4-one (NU7441), a potent inhibitor of DNA-dependent protein kinase (DNA-PK; IC50 = 42 ± 2 nM), have been synthesized in which water-solubilizing groups [NHCO(CH₂)nNR¹R², where n = 1 or 2 and the moiety R¹R²N was derived from a library of primary and secondary amines, e.g., morpholine] were placed at the 1-position. Several of the newly synthesized compounds exhibited high potency against DNA-PK and potentiated the cytotoxicity of ionizing radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…The newly synthesised compounds all possessed polar substituents at the dibenzothiophene 1-position, with an aim to improve potency and physicochemical properties [30]. A number of the compounds exhibited high potency against DNA-PK and potentiated the cytotoxicity of IR in vitro 10-fold or more (e.g., 14; DNA-PK IC 50 =5.0 ± 1 nM, IR dose modification ratio=13).…”
Section: (Scheme 4)mentioning
confidence: 99%
See 1 more Smart Citation
“…The newly synthesised compounds all possessed polar substituents at the dibenzothiophene 1-position, with an aim to improve potency and physicochemical properties [30]. A number of the compounds exhibited high potency against DNA-PK and potentiated the cytotoxicity of IR in vitro 10-fold or more (e.g., 14; DNA-PK IC 50 =5.0 ± 1 nM, IR dose modification ratio=13).…”
Section: (Scheme 4)mentioning
confidence: 99%
“…Furthermore, 14 was shown to potentiate not only IR in vitro but also DNA-inducing cytotoxic anticancer agents, both in vitro and in vivo. A counter-screen against other members of the PI3K PIKK family revealed that some of the compounds were potent mixed DNA-PK and PI3K inhibitors, including 14 [30,31]. The favourable biological activity of 14 was complemented by superior drug-like properties compared to NU7441 (13), and acceptable plasma protein binding, combined with weak activity against hERG and a panel of cytochrome P450 (CYP) drug-metabolising enzymes (Table 4) [30].…”
Section: (Scheme 4)mentioning
confidence: 99%
“…[a] Data are the mean±SD or individual values; adapted from Cano et al . [b] DMR: dose modification ratio, defined as the percentage of cell survival in the absence of compound with 2 Gy treatment divided by that in the presence of compound plus 2 Gy treatment as determined in 6‐ to 8‐day clonogenic assays.…”
Section: Small‐molecule Inhibitors Of Dna‐pk Activitymentioning
confidence: 99%
“…25 The two nitrophenyl derivatives (15,16) were then quantitatively reduced by zinc in acetic acid to the corresponding amino derivatives (18,19). 26 …”
Section: Chemistrymentioning
confidence: 99%